Rhinovirus Outbreak in a Long Term Care Facility for Elderly Persons Associated with Unusually High Mortality - Louie, Janice K. (Clin Infect Dis, 2005)
During a 6-week period in 2003, 56 residents and 26 staff developed respiratory illness in a long-term facility; 12 residents died. Seven of 13 respiratory specimens were culture-positive for rhinovirus; 6 of the isolates were serotype 82. In elderly populations, severe illness may be associated with organisms typically considered to be “benign,” such as rhinovirus.